Invasive Papillary Breast Carcinoma - S.J. Bhosale; A.Y. Kshirsagar; S.R. Sulhyan; S.V. Jagtap; Y.P. Nikam (Case Reports in Oncology, 2010)
We present the case of a 55-year-old postmenopausal female who presented with complaints of a gradually increasing painless subareolar mass in the left breast of 4 months’ duration. Left-sided modified radical mastectomy was performed and the specimen was histopathologically diagnosed as invasive papillary carcinoma. Immunohistochemistry confirmed this diagnosis. All 8 excised axillary lymph nodes were negative for malignant cells. Postoperative chemotherapy was given and for the past 6 months, the patient has maintained a regular follow-up on an outpatient basis. She does not have any evidence of either local or distant recurrence of tumour metastases.